Development of indigenous knowledge-based teaching materials on water cycle topic - Salsabila, Annisa; Meilinda; Nazip, Khoiron; Riyanto; Wulandari, Ratu Mutiara (Biosfer: Jurnal Pendidikan Biologi, 2024)
This study aims to develop indigenous knowledge-based teaching materials on water cycle topics under basic competencies 3.10 and 4.10 in junior high schools. The method used in this research is the type II developmental research of Richey & Klein consisting of the exploration and evaluation stages (trial). This research was conducted in two cycles of evaluation. The results of the development of teaching materials were tested for validity by 5 validators, readability was tested to sixteen students using the gap test. Based on the research results, the validation value for the development of the teaching materials was 4.36 which falls into the very valid category. The readability test results were 91.17% and when converted using Bormuth criteria, it means that the product is easy to understand. In conclusion, this teaching material applies to junior high school students, particularly the water cycle topic.